Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/ejo/cjp047
|View full text |Cite
|
Sign up to set email alerts
|

Initial forces generated by three types of thermoplastic appliances on an upper central incisor during tipping

Abstract: The force properties of thermoformed appliances have not been systematically investigated. Therefore, the aim of the present study was to quantify the forces delivered by thermoplastic appliances manufactured from three different materials, with the same thickness, on a central upper incisor, during tipping. Five identical appliances were manufactured from three different materials all with a thickness of 1.0 mm (Ideal Clear, Erkodur, and Biolon). For measuring the forces, an isolated measuring tooth, as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 23 publications
2
53
0
12
Order By: Relevance
“…[17][18][19] Nevertheless, the forces at the lower range of activation are of lesser relevance, because the amount of movement is adapted to the width of the periodontal ligament (0.1-0.3 mm). 20,21 As postulated before, 5,6 a self-protecting mechanism might be responsible for a low rate of root resorption, even with appliances with an initial activation range of over 0.2 mm. 4,[17][18][19] This mechanism is probably based on the reduced fit of the appliance during increased activation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…[17][18][19] Nevertheless, the forces at the lower range of activation are of lesser relevance, because the amount of movement is adapted to the width of the periodontal ligament (0.1-0.3 mm). 20,21 As postulated before, 5,6 a self-protecting mechanism might be responsible for a low rate of root resorption, even with appliances with an initial activation range of over 0.2 mm. 4,[17][18][19] This mechanism is probably based on the reduced fit of the appliance during increased activation.…”
Section: Discussionmentioning
confidence: 91%
“…16 Comparable values and Fz values about three times higher than those measured in the present study have been reported before, for the same materials, during tipping of 0.151 mm. 5 These intrusive force can be explained by a local deformation of the inclined inner surfaces of the appliance ( Figure 5) and with a reduced fit during progressive axial rotation, which tends to deform the appliance like a bow, by raising it in the anterior region. As a consequence, a reactive force Fz is generated that acts vertically on the tooth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Although such study design allows a basic comparison between the various plastic materials, it must be noted that results cannot be transferred to the clinical situation because of the simplified specimen geometry that ignores relevant mechanical effects such as regional reinforcement of the plastic material due to thermoforming on dental models. 11,12 The latter has been considered in later investigations examining force-andmoment application of aligners thermoformed on dentition models. Results clearly indicated that the teeth are overloaded when following the recommendations regarding tooth displacements in the setup and aligner materials.…”
Section: Introductionmentioning
confidence: 99%